Acute effect of low and high glycemic index meals on post- prandial glycemia and insulin responses in patients with type 2 diabetes mellitus - Mohd Yusof, Barakatun Nisak; Abd Talib, Ruzita; A. Karim, Norimah; Kamarudin, Nor Azmi; Arshad, Fatimah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction:Post-prandial hyperglycemia is an important independent risk factor in the development of cardiovascular disease in diabetes. This randomised cross-over study was conducted to compare the post-prandial glycemic and insulin responses to both high and low glycemic index (GI) meals in patients with type 2 diabetes (T2DM). Methods:A total of 41 patients with established T2DM (16 males, 25 females, Age= 55 + 10 years and BMI= 27 + 4 kg/m2) were randomly given either a High GI or a Low GI meal in a cross-over manner. Both test meals were separated by one week washout periods. The meals contained almost the same amount of energy and macronutrients with the exception of the GI values(High GI=70 vs Low GI= 36). Venous blood was taken through an indwelling catheter periodically at 0, 30, 60, 90, 120, 150 and 180 minutes respectively. The incremental area under the curve (iAUC) was used to calculate the post-prandial glycemia and insulin excursion over the 3-hour period. Results: The low GI meal induced lower glycemic responses at times 30, 60, 90 and 120 minutes (mean+SE; low GI=8.1+0.4, 9.1+0.4, 8.9+0.4 and 8.5 +0.4mmol/l vs high GI= 9.1+0.4, 10.7+0.4, 11.0+0.5 and 9.7 +0.5 mmol/l) and reduced the insulin levels at time 60, 90, 120 and 150 minutes (mean+SE; low GI= 17.1+1.7, 21.1+2.0, 20.4+1.7,18.5+1.8 vs high GI= 25.0+2.5, 31.2+2.9, 29.8 +3.0 and 23.0+2.3 μIU/ml)(p<0.05). The area under the glycemic (mean+SE; low GI= 215.93 + 15.9 mmol.L/minute vs high GI= 419.52 + 32.7 mmol.L/minute) and insulin (mean +SE; low GI= 1439.76 + 226 vs high GI= 2372.76 + 317μ IU.ml/min) curves were lower after the low GI than high GI meal respectively (p<0.05).Conclusion: The low GI meal has the ability to reduce the post-prandial hyperglycemia as well insulin responses in type 2 diabetes patients.